THE EFFECTIVENESS OF USING QRIS TECHNOLOGY ON TAX COLLECTION : STUDY ON REGISTERED SMEs AT KPP KARANGPILANG SURABAYA - Pramudianti, Mira; Hendrawati, Erna; Abidin, Khoirul (IJOSMAS, 2023)
Tax is the main state revenue, to overcome state expenditure it is the largest source of tax. The government varies greatly in the types of taxes according to the tax objects faced or experienced by taxpayers. Taxpayers are tax subjects who pay taxes and report taxes based on calculations by the taxpayer or the Fiscus. Tax collection is mainly based on the Self Assessment tax collection system where taxpayers calculate themselves and pay and report tax on tax objects that occur to the taxpayer. Tax for MSMEs is the final tax that adheres to the Self Assessment System of the tax objects owned by the taxpayer. MSMEs are based on turnover or gross sales that occur each month or period. MSME tax is actually income tax article 4 paragraph 2, the practice of which is further regulated through Government Regulation number 23 of 2018 (PP 23/2018). MSMEs (Micro, Small and Medium Enterprises (MSMEs) are an important pillar in the economy. MSMEs are one part of the driving wheel of the people's economy that cannot be underestimated. This is in accordance with the statement by Yustinus Prastowo, special staff to the Minister of Finance, in (Elena, 2020) stated that the existence of MSMEs is a sector that has strong resilience and is even the backbone of economic growth. In order to optimize tax revenues from the MSME sector, innovation from the DJP is of course needed to increase tax compliance from MSME actors. So far, the MSME tax collection process is for MSME actors to calculate themselves from their turnover. they earn then periodically pay their taxes every month and report it to the DJP, namely by using the self-assessment method. Alternatives others, such as the implementation of withholding tax on MSMEs in e-commerce, which has great potential, has not yet been implemented (Wicaksono, 2018). This method, which according to the DJP is quite easy and practical, apparently does not necessarily result in a significant increase in MSME taxpayer compliance. After PP Number 23 of 2018 concerning Income Tax on Income from Businesses Received or Obtained by Taxpayers Who Have a Certain Gross Turnover, which cuts PPh UMKM final from 1% to 0.5%, tax revenues from MSMEs even tend to decrease even though quantitatively the number of MSME taxpayers who pay taxes and report them has increased (Santoso, 2019). The implementation of QRIS (Quick Response Code Indonesian Standard) has brought many The benefits and convenience of the payment system need to be considered by the DGT. Therefore, it is necessary to immediately conduct a study regarding the perception of MSME actors towards QRIS technology so that it can be known how big the potential of QRIS is in simplifying the MSME taxation system which ultimately has an impact on optimizing tax revenues from the MSME sector. In a payment system, QR codes are a technological development which can help the device to send a number of data so that the activities carried out can be carried out efficiently, quickly and practically, especially in financial payment transactions